2011
DOI: 10.1136/bmjqs-2011-000218
|View full text |Cite
|
Sign up to set email alerts
|

What drives hospital performance? The impact of comparative outcome evaluation of patients admitted for hip fracture in two Italian regions

Abstract: The Lazio and Tuscany programmes appeared to have a positive impact on quality of care for older patients admitted with hip fracture without having a negative impact on other orthopaedic interventions. The results highlight the need for continuous quality improvement by repeating the evaluation process and by combining the performance system with a management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
(26 reference statements)
0
31
0
1
Order By: Relevance
“…This finding is especially true for hospitals entirely paid by the DRG system, as shown in a study that compared the quality improvement programs in Lazio and Toscana [16]. …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This finding is especially true for hospitals entirely paid by the DRG system, as shown in a study that compared the quality improvement programs in Lazio and Toscana [16]. …”
Section: Discussionmentioning
confidence: 92%
“…The impact of pay-for-performance in the Lazio region can be related to the fact that the hospitals had plenty of room for improvement from baseline [17], given the low proportion of patients receiving surgery within 48 hours [16]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more and more authors in the healthcare literature raise increasing expectation on the public disclosure of data (Leatherman and McCarty 1999;Marshall et al 2000;Hibbard et al 2003;Rogowski et al 2004), this factor may be even more effective if associated with others. Indeed, Pinnarelli et al (2012) demonstrated that in Italy only two regions improved the percentage of femur fracture operated within 48 h: Lazio and Tuscany. Both of these two Regions decided to publicly disclose data, however improvement registered by Tuscany was significantly higher than Lazio because of the more comprehensive strategy implemented by Tuscany Region.…”
Section: The Critical Factors Leading To Successmentioning
confidence: 99%